Deep sequencing of the TP53 gene reveals a potential risk allele for non–small cell lung cancer and supports the negative prognostic value of TP53 variants. Issue 2 (February 2017) - Deben, Christophe; Van den Bossche, Jolien; Van Der Steen, Nele; Lardon, Filip; Wouters, An; de Beeck, Ken Op; Hermans, Christophe; Jacobs, Julie; Peeters, Marc; Van Camp, Guy; Rolfo, Christian; Deschoolmeester, Vanessa; et al.
The TP53 gene remains the most frequently altered gene in human cancer, of which variants are associated with cancer risk, therapy resistance, and poor prognosis in several tumor types. To determine the true prognostic value of TP53 variants in non–small cell lung cancer, this study conducted further research, particularly focusing on subtype and tumor stage. Therefore, we determined the TP53 status of 97 non–small cell lung cancer adenocarcinoma patients using next generation deep sequencing technology and defined the prognostic value of frequently occurring single nucleotide polymorphisms and mutations in the TP53 gene. Inactivating TP53 mutations acted as a predictor for both worse overall and progression-free survival in stage II–IV patients and patients treated with DNA-damaging (neo)adjuvant therapy. In stage I tumors, the Pro-allele of the TP53 R72P polymorphism acted as a predictor for worse overall survival. In addition, we detected the rare R213R (rs1800372, minor allele frequency: 0.0054) polymorphism in 7.2% of the patients and are the first to show the significant association with TP53 mutations in non–small cell lung cancer adenocarcinoma patients (p = 0.003). In conclusion, Our findings show an important role for TP53 variants as negative predictors for the outcome of non–small cell lung cancer adenocarcinoma patients, especially for TP53 inactivating mutations in advanced stage tumors treated with DNA-damaging agents, and provide the first evidence of the R213R G-allele as possible risk factor for non–small cell lung cancer.